Modern modes of chronic hepatitis B treatment in daily clinical practice - M. V. Mayevskaya; M. A. Morozova; S. A. Ondos; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review and clinical case. To bring modern standards of antiviral therapy (AVT) of chronic hepatitis B (CHB) and possible mistakes at assessment of medical tactics to focus of general practitioners.Summary. Chronic hepatitis B still remains one of the most actual problems in hepatology. The main aim of treatment is improvement of patients quality of life and prognosis of disease that can be achieved at permanent suppression of virus replication. The modern modes of AVT have several variants: treatment for the limited term by interferon-alpha or nucleotides/ nucleosides analogues and long-term treatment by nucleotides/nucleosides analogues. The major factor decreasing nucleotides/nucleosides AVT efficacy is virus resistance development. At application of pegilated interferon (PEG-IFN) resistance does not develop, however frequency of adverse events is high. The low level of virologic response at of PEG-IFN treatment should be mentioned as well. Nowadays detailed international and Russian guidelines on with chronic hepatitis B patient management are developed. Despite of them general practitioners quite often experience difficulties at choice of medical approach. This article reviews in brief up-to-date modes of CHB treatment, clinical case demonstrating the basic AVT stages is presented: decision-making on its onset, monitoring of the patient during treatment, rules of choice and substitution of antiviral agents, criteria of treatment response assessment and indications for its termination.Conclusion. The adequate choice of drug at definition of antiviral treatment approach allows to suppress virus replication effectively, reduces risk of resistance development and rate of side effects while violation of international standards can result in fatal outcome. The presented clinical case evidently shows possible mistakes at chronic hepatitis B patient management and their consequences.